Pojok Literasi Dalam Meningkatkan Minat Baca Siswa-Siswi SD N Sulang - Ardanamesti, Sagung Rahma (LPPM Universitas Pamulang, 2024)
The real work lecture has been held in Sulang Village ,Dawan District, Klungkung regency, Bali which was held for 27 days which began on January 16 to February 11, 2023. Literacy ability is one of the most important in the world of education, in this case SD N Sulang wants to increase the interest in reading its students. By utilizing the literacy corner media developed by the Sulang Village KKN group, it is hoped that it can help increase the interest in reading for SD N Sulang students. It is hoped that this program can be continued even though the KKN period has ended, so that the interest in reading students of SD N Sulang can be awakened and make reading a good habit.